Whistle Blowing, Forced CEO Turnover, and Misconduct: The Role of Socially Minded Employees and Directors - Bereskin, Frederick; Campbell, Terry; Kedia, Simi (Management Science, 2020)
We examine the response of prosocial employees and boards of directors to corporate misconduct. We develop several proxies for the presence of prosocial employees and directors based on the density of social networks and social capital in the county of the firms’ headquarters and companies’ relevant corporate social responsibility ratings. We document that proxies for prosocial employees and directors are associated with an increase in whistle blowing and forced chief executive officer turnover in a sample of firms that engage in misconduct. The higher expected cost of misconduct in firms with prosocial employees is associated with a lower likelihood of misconduct. Our findings highlight the role of nonfinancial imperatives of employees and directors in mitigating misconduct. This paper was accepted by Suraj Srinivasan, accounting.